Credit Based Marketing Mechanism Regulates the Base Shiftment of Farmers - Dr. Sini Raj S (International Journal of Advanced Science and Technology, 2020)
The members of the credit society should be able to sell their produce through marketing society, and the primary credit society should act as the agent of the marketing society and assemble and arrange transport to marketing society. The first step in the process of linking of credit with marketing is the application of agricultural credit societies to marketing societies. Now, the primary credit society advances crop loans to the member on the understanding that they would sell their produce through the marketing society. This system of mutual assistance was expected to ensure better recoveries for the primary societies and better business for the marketing societies.